Jiuding capital : private equity form with Chinese characteristics - Meng, Fei; Jia, Ning; Tian, Xuan ([London] : SAGE, 2016)
On December 9th, 2010, 'The 10th China Venture Capital & Private Equity Annual Forum' organized by Zero2IPO was held in Hyatt on the Bund in Shanghai, attracting the eyeballs of thousands of professionals in the industry. Since 2008 when the dominance of foreign private equity funds (PEs) in the Chinese market was weakened, local PEs are rising rapidly and becoming a new force of the industry. The most eyeball-catching one is the winner of four big prizes at the forum - Jiuding Capital.
Originally Published in: Zhao, Z., Liao, L., & Jia, N. (2011). Jiuding Capital: Private Equity Firm with Chinese Characteristics. 0-310-111. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Jiuding Capital (Firm); Investment banking -- Case studies; Venture capital -- Case studies; Strategic planning -- Case studies